An Exploration of Ethics-Based Leadership in Human Resource Management at Institutions of Early Childhood Education - Ade Wawan (Journal of Childhood Development, 2022)
This research aims to investigate the role of ethics-based leadership in human resource management within early childhood education of Ma'arif institutions Lampung. The study explores how ethical principles in leadership influence human resource management, the quality of educational services, and child development in these institutions. The research methodology employed involves interviews, observations, and document analysis. The results of this study are expected to provide deeper insights into the significance of ethics in leadership within early childhood education institutions and its contribution to holistic child development. This research holds practical implications for enhancing the quality of early childhood education through an ethically grounded human resource management approach